Merging energy-based design criteria and reliability-based methods exploring a new concept. - Ghosh, Siddhartha (Earthquake engineering & structural dynamics.)
This paper examines the potential development of a probabilistic design methodology, considering hysteretic energy demand, within the framework of performance-based seismic design of buildings. This article does not propose specific energy-based criteria for design guidelines, but explores how such criteria can be treated from a probabilistic design perspective. Uniform hazard spectra for normalized hysteretic energy are constructed to characterize seismic demand at a specific site. These spectra, in combination with an equivalent systems methodology, are used to estimate hysteretic energy demand on real building structures. A design checking equation for a (hypothetical) probabilistic energy-based performance criterion is developed by accounting for the randomness of the earthquake phenomenon, the uncertainties associated with the equivalent system analysis technique, and with the site soil factor. The developed design checking equation itself is deterministic, and requires no probabilistic analysis for use. The application of the proposed equation is demonstrated by applying it to a trial design of a three-storey steel moment frame. The design checking equation represents a first step toward the development of a performance-based seismic design procedure based on energy criterion, and additional works needed to fully implement this are discussed in brief at the end of the paper.